Evolutionary and expression analyses reveal a pattern of ancient duplications and functional specializations in the diversification of the Downstream of Kinase (DOK) genes. (July 2018) - Guittard, Geoffrey; Pontarotti, Pierre; Granjeaud, Samuel; Rodrigues, Magda; Abi-Rached, Laurent; Nunès, Jacques A.
Abstract: Downstream of Kinase (DOK) proteins represent a multigenic family of adaptors that includes negative regulators of immune cell signaling. Using phylogenetics and intron/exon structure data, we show here that the seven human DOK genes ( DOK1 to DOK7 ) form three highly divergent groups that emerged before the protostome-deuterostome split: DOK1/2/3, DOK4/5/6, and DOK7 . For two of these three groups ( DOK1/2/3 and DOK4/5/6 ), further gene duplications occurred in vertebrates and so while chordates only have three DOK genes, vertebrates have seven DOK genes over the three groups. From our expression analysis in humans, we show that each group of DOK genes has a distinct pattern of expression. The DOK1/2/3 group is immune specific, yet each of the three genes in the group has a distinct pattern of expression in immune cells. This immune specificity could thus be ancestral, with the DOK1/2/3 gene also being immune-related in protostomes. The DOK4/5/6 and DOK7 groups represent genes that are much less expressed in immune system than the DOK1/2/3 group. Interestingly, we identify a novel tyrosine based motif that is specific to the vertebrate DOK4 /5/6 sequences. The evolution of the DOK genes is thus marked by a pattern of ancient duplications and functional specializations. Highlights: DOK genes form three highly divergent groups that emerged before the protostome-deuterostome split. DOK genes are differentially expressed in human and mouse immune cells. Proteins encoded by DOK4/5/6 genes are containing a conserved tyrosine-based motif.